Assessment of the utility of chitosan nanoparticles and microfibers in drug delivery applications of sulfamethoxazole and ciprofloxacin - Nussara Soontorntepwarakul; Kanokthip Boonyarattanakalin; Poowadon Fukasem; Sitthinan Somkhuan; Kasama Srirussamee; Kiattawee Choowongkomon; M. Paul Gleeson (New Journal of Chemistry, 2025)
The encapsulation of antibiotic drugs sulfamethoxazole and ciprofloxacin in chitosan nanoparticles and microfibres was systematically investigated in terms of their loading capacity and release profile.
Keywords: Drug Solubulity and Delivery Systems; Advanced Drug Delivery Systems; Advancements in Transdermal Drug Delivery